Face Recognition Application Using the Eigenface Method for Employee Attendance at STMIK Budi Darma - Alwin Fau; Fince Tinus Waruwu (IJISTECH (International Journal of Information System and Technology), 2020)
Attendance is one of the most important repetitive transactions because it is related to the productivity of employees and employees and is one of the controlling indicators Human resources (HR) which aim to increase the potential of human resources as well used in the framework of efficiency. Current technological developments allow making a system that can assist humans in recognizing a digital image. One of them, a field that is currently being developed is pattern recognition. This technology identifies the special physical characteristics of a person. An example of pattern recognition is an example of face recognition, iris recognition, fingerprint recognition (finger recognition), and others. The face is part of the human body to be the focus of attention in social interactions. The face has a very important role that can show someone's identity; therefore a face can be used as a part of the human body that is used as an indication of knowing someone or face recognition. Attendance is an administrative act regarding attendance and absence attendance of employees. In this facial recognition, research uses a camera to capturing someone's face was then compared to the face that had previously been stored in a specific database. Broadly speaking, the process of facial recognition is the webcam camera captures the face. Then we get an R (read) value, G (Green), B (Blue). Using pre-processing, cropped, RGB to grayscale. After the Grayscale process is carried out, the face processing stage is carried out using the eigenface method. In this eigenface method, there are several core stages namely: converting faces to matrices, calculating Flat Vector averages, determining values eigenface, and perform the face identification process by looking for the eigenface value approaching. One of the ways of facial recognition can be developed into an application absence that can be applied in companies to prevent manipulation of absences by employees or employees.